Methodology for evaluating special fitness and competitive activity of highly skilled kayakers - Kolumbet, A.; Klymenko, H.; Natroshvili, S. G.; Korop, M.; Bystra, I.; Gamov, I. (Journal of Physical Education and Sport, 2023)
Purpose Development of methodology for individual evaluating special fitness and competitive activity of highly skilled kayakers.